ANALISIS USAHA KECIL MANENGAH PENGOLAHAN MINYAK KELAPA RAKYAT DI KECAMATAN SUNGAI BATANG KABUPATEN INDRAGIRI HULIR - Yadi, Sapri; Hadi, Syaiful; Muwardi, Didi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The purpose of this study was to determine the development of Small and Medium Enterprises (SMEs) and know the cost, revenue, efficiency, and the turning point of SME capital coconut oil processing in District Sungai Batang. Determination of sample areas is done intentionally (purposive sampling) with consideration District of Sungai Batang is an area that is still a lot of oil processing SMEs than that seen from the trenches conditions of transport and farm roads damaged and neglected. The number of respondents for SMEs oil processing as much as 8 people entrepreneurs. improve this translation primary data and secondary data. Data was collected through observation, interviews and recording. These results indicate that during the period 2010-2014 the number of SMEs oil processing in Sungai Batang continued to decline with total growth declineed by -6.72% per year, the average total cost incurred by employers oil processing are sold in Sungai Batang for Rp.153.768, average profit earned by Rp.93.232 coconut oil businessmen. RCR SMEs oil processing an average of 1.62, which means coconut oil processing business is profitable and feasible to be developed. The turning point capital small and medium businesses already profitable palm oil processing. Â Keywords: Small Medium Enterprises, Coconut Oil.